Hypoglossal Nerve Stimulation in Veterans with Obstructive Sleep Apnea. (14th December 2019) - Sarber, Kathleen M.; Chang, Katherine W.; Epperson, Madison V.; Tabangin, Meredith E.; Altaye, Mekibib; Ishman, Stacey L.; Dhanda Patil, Reena
Abstract : Objectives: The hypoglossal nerve stimulator (HNS) is an effective treatment for obstructive sleep apnea (OSA) in a relatively healthy subset of the population. Our aim was to determine the efficacy of HNS in a veteran population with a high incidence of chronic disease and mental health disorders. Our secondary aim was to compare subjective outcomes and adherence between veterans with and without mental health disorders. Methods: We included all patients who underwent HNS at our institution to date. Veterans were divided into two groups based on whether or not they carried a diagnosis of anxiety, depression, and/or post‐traumatic stress disorder. Demographics, comorbidities, previous OSA treatments, adverse events, and adherence to therapy were recorded. Baseline and treatment outcome data were collected and analyzed including polysomnographic parameters, Epworth sleepiness scale score (ESS), and body mass index. Results: Thirty‐one patients were identified: 93.5% male, median age = 63.0 years. Median apnea hypopnea index (AHI) decreased from 30.0 to 3.0 events/hour ( P < .001) and median ESS dropped from 11.0 to 6.5 ( P < .001). There was no difference between groups with regard to change in AHI or ESS ( P = .31 and .61). Twenty‐six (89.7%) patients achieved surgical success (decrease in AHI > 50% and AHI < 20 events/hour) and 21 (72.4%) had AHI < 5 events/hour. The mean device usage was 5.4 hours/night which was not significantly different between groups ( P = .55). Conclusion: Our cohort exhibited similar declines in AHI and ESS compared to published studies with adequate adherence to HNS. There were no significant differences in ESS or adherence to therapy between veterans with and without mental health disorders. Level of Evidence: 4 Laryngoscope, 130:2275–2280, 2020